1977
DOI: 10.1056/nejm197709152971101
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Production of Chorionic Gonadotropin and Its Subunits by Islet-Cell Tumors

Abstract: We measured human chorionic gonadotropin (hCG) and its subunits in 76 patients with islet-cell tumors. Seventeen of 27 patients with functioning islet-cell carcinomas had elevated plasma levels of hCG or one of its subunits (hCG-alpha and hCG-beta). Secretion was often discordant; the most frequent finding was an elevated level of hCG-alpha alone. In one patient responding to streptozocin, changes in hCG-alpha correlated with the clinical course. Studies of tumor extracts suggested that the markers observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…In a previous study, the hCG-like material found in urine and blood from patients with germ cell tumours appeared to be mainly intact hCG, while material from the patient with a metastatic bladder tumour consisted principally of free beta subunit (Norman et al, 1985). Variability of the relative concentration of intact hormone and free subunits, together with heterogeneous glycosylation of the protein chains, has also been reported in studies on patients with a variety of other tumour types (Weintraub & Rosen, 1973;Rosen & Weintraub, 1974;Kahn et al, 1977;Yoshimoto et al, 1979b). The degree of glycosylation affects various biochemical characteristics and also the rate of metabolism in vivo (Van Hall et al, 1971;Tsuruhara et al, 1972).…”
Section: Resultsmentioning
confidence: 73%
“…In a previous study, the hCG-like material found in urine and blood from patients with germ cell tumours appeared to be mainly intact hCG, while material from the patient with a metastatic bladder tumour consisted principally of free beta subunit (Norman et al, 1985). Variability of the relative concentration of intact hormone and free subunits, together with heterogeneous glycosylation of the protein chains, has also been reported in studies on patients with a variety of other tumour types (Weintraub & Rosen, 1973;Rosen & Weintraub, 1974;Kahn et al, 1977;Yoshimoto et al, 1979b). The degree of glycosylation affects various biochemical characteristics and also the rate of metabolism in vivo (Van Hall et al, 1971;Tsuruhara et al, 1972).…”
Section: Resultsmentioning
confidence: 73%
“…Recently other grouips have also documented increases in a levels in benign as well as malignant conditions (Dosogne-Guerin et al, 1978;Braunstein et al, 1979). These observations are at variance with results of a study of patients with pancreatic islet-cell tumours, in which serum of subunit was high only in malignant tumours, and normal in benign cases (Kahn et al, 1977).…”
Section: Resultsmentioning
confidence: 84%
“…Recent studies, for example, have shown that the presence of the alpha chain of human chorionic gonadotropin (HCG) both in the plasma and in tissues is highly predictive of malignant behavior in these tumors (23). Biological behavior may also be correlated with the major hormonal species secreted by the tumor (6).…”
Section: Pancreatic Endocrine Cellsmentioning
confidence: 99%
“…These widely dispersed cells contain a set of common enzymes, including neuron-specific enolase (34). It has also become apparent that many of the gut hormones are also present within the nervous system where they arè Presented as part of the program at the 1982 Joint Meeting of the American and Japanese Histochemical Societies, held in Vancouver, British Columbia, Canada, July [20][21][22][23][24]1982.…”
Section: Introductionmentioning
confidence: 99%